2009
DOI: 10.1016/j.jtcvs.2009.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic segmentectomy for stage I non–small-cell lung cancer: Comparison of video-assisted thoracic surgery versus open approach

Abstract: Video-assisted thoracic surgery segmentectomy can be performed with acceptable morbidity, mortality, recurrence, and survival. The video-assisted thoracic surgery approach affords a shorter length of stay and fewer postoperative pulmonary complications compared with open techniques. The potential benefits and limitations of segmentectomy will need to be further evaluated by prospective, randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 42 publications
3
55
0
4
Order By: Relevance
“…Flores et al [6] reported that the prognosis after VATS lobectomy for clinical stage IA NSCLC did not differ significantly from that after lobectomy by thoracotomy, and that VATS lobectomy was superior in terms of the incidence of complications and length of hospital stay. Similarly, Schuchert et al [7] showed that the prognosis after VATS segmentectomy was similar to that after open segmentectomy, and that VATS segmentectomy was associated with fewer postoperative complications. Yamashita et al [8] also reported that the prognosis for stage I NSCLC after VATS lobectomy was similar to that after VATS segmentectomy.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Flores et al [6] reported that the prognosis after VATS lobectomy for clinical stage IA NSCLC did not differ significantly from that after lobectomy by thoracotomy, and that VATS lobectomy was superior in terms of the incidence of complications and length of hospital stay. Similarly, Schuchert et al [7] showed that the prognosis after VATS segmentectomy was similar to that after open segmentectomy, and that VATS segmentectomy was associated with fewer postoperative complications. Yamashita et al [8] also reported that the prognosis for stage I NSCLC after VATS lobectomy was similar to that after VATS segmentectomy.…”
mentioning
confidence: 85%
“…Today, few surgeons are opposed to VATS procedures to treat clinical stage I NSCLC. VATS is superior to thoracotomy in that it is less invasive, results in fewer postoperative complications, and offers a better quality of life and an earlier return to society, and appropriate patient selection is associated with a favorable prognosis [6][7][8][9][10][11]. The limitations of this study are that, since it was a retrospective study, background factors varied with the procedure, and the duration of follow-up was relatively short.…”
mentioning
confidence: 94%
“…However reasonably sized series of uniportal segmentectomy are sparingly reported (13)(14)(15)(16) (19) whose analysis of 225 consecutive segmentectomies also found a reduced incidence of pulmonary complications in the VATS group. Shorter chest tube duration following VATS segmentectomy has likewise been reported (2).…”
Section: Discussionmentioning
confidence: 99%
“…VATS segmentectomy is now more frequently utilised in the management of lung cancer resection (19)(20)(21)(22)(23), although is often reserved for patients with poor operability (24). Studies thus far have shown equivalent oncological outcomes to open segmentectomy with no significant differences in locoregional recurrence or overall survival (25).…”
Section: Discussionmentioning
confidence: 99%
“…VATS has gained increasing acceptance not only for pulmonary lobectomies but also for more challenging procedures like sublobar resections in early stage lung cancer [7][8][9][10][11]. Recently, some series have suggested that VATS is a safe approach even for the treatment of advanced tumors (stage IIIA NSCLC) in which induction therapy and extended procedures like bronchial sleeve resections are indicated [8,12].…”
Section: Discussionmentioning
confidence: 99%